355 Use of Novel Telemedicine Software to Automate Cranial Nerve and Neuro-Ophthalmic Remote Testing. (1st April 2022) - Mouchtouris, Nikolaos; Yu, Si Yuan; Karsy, Michael; Sergott, Robert; Moster, Mark; Farrell, Christopher J.; Evans, James J.
Abstract : INTRODUCTION: Despite the rapid surge in telemedicine use due to the COVID-19 pandemic, there is still a paucity of telemedicine tools for the remote assessment of patients with neurological diagnoses. Current telemedicine platforms lack the capabilities to perform thorough cranial nerve and neuro-ophthalmic testing. To address this need, we developed a novel software that patients can use to undergo cranial nerve and neuro-ophthalmic testing remotely via their own personal computer. METHODS: We conducted a pilot study of patients above 18 years old diagnosed with a brain tumor who receive their care at our institution. Ten patients were enrolled to undergo a comprehensive cranial nerve and neuro-ophthalmic testing using our proprietary telemedicine software. We assessed visual acuity, visual fields, extraocular movements, facial sensitivity, facial symmetry, hearing, uvula/palatal movement, shoulder elevation, tongue deviation, and speech. Their performance on the telemedicine software to physical examination by their treating physician. All patients were given a patient satisfaction survey upon completion of the telemedicine visit. RESULTS: Ten patients have been enrolled so far with a mean age of 47±14.3 years old (4 males, 6 females). Diagnoses included brain metastases, pituitary adenoma, craniopharyngioma and meningiomas. Visual acuity, facial sensitivity, facial symmetry, shoulder elevation, tongue deviation were consistent with physical examination findings in all six patients. Extraocular movements were consistent in 80% of patients. Assessment of the uvula was the most challenging, comparable to physical examination in only 20% of patients. Visual fields were equivalent in 80% of patients and superior than confrontation testing in 10% of patients. CONCLUSION: While this is a very early experience with a new telemedicine software, we demonstrate the feasibility of performing comprehensive cranial nerve and neuro-ophthalmic testing. We provide a detailed account of the challenges encountered, the patient experience and satisfaction results.